Knowledge, attitudes, and practices (KAP) regarding occupational protection among orthopedic theatre nurses using orthopedic power tools (OPTs): A cross-sectional study - Hang Li; Zhao-Li Guo; Tao Chen; Wen-Qian Wang; Zheng Gao (PLoS ONE, 2026)
Introduction The objective of this study was to explore the factors associated with the knowledge, attitudes, and practices (KAP) of orthopedic theatre nurses with regard to occupational protection when orthopedic power tools (OPTs) are used to provide a reference for ensuring the occupational safety of nurses working in orthopedic surgery rooms. Methods This cross-sectional survey involved 272 orthopedic theatre nurses across eight tertiary hospitals in Shanxi Province, China, between September and December 2024. An occupational protection assessment tool that was self-developed and included 3 dimensions (Knowledge, Attitude, and Practice), containing a total of 45 items, was utilized among operating theatre nurses with OPTs. Results The median as the cutoff, 52.9% (144/272) of respondents had an adequate Knowledge score, while 47.1% (128/272) had a good score; 54.0% (147/272) of the respondents had a positive Attitude score, and 46.0% (125/272) had a negative attitude; 53.7% (146/272) of the participants demonstrated good performance in the Practice score, whereas 46.3% (126/272) showed poor performance. Multivariable regression analysis revealed that the knowledge scores of those with a bachelor’s degree (aOR=7.040; 95% CI: 3.204–15.466; p < 0.001), senior professional title (aOR=5.216; 95% CI: 1.228–22.155; p = 0.025), occupational protection training frequency less than 6 months (aOR=10.085; 95% CI: 4.146–24.533; p < 0.001) or 6–12 months (aOR=6.550; 95% CI: 3.262–13.153; p < 0.001) and actively consulting the latest professional protection knowledge (aOR=2.652; 95% CI: 1.426–4.931; p = 0.002) were higher and statistically significant. Senior title (aOR=5.226; 95% CI: 1.409–19.387; p = 0.013), occupational exposure (aOR=2.770; 95% CI: 1.484–5.169; p = 0.001) and Knowledge scores (aOR=2.663; 95% CI: 1.581–4,448; p < 0.001) yielded attitude scores that were higher and statistically significant. Attitude scores (aOR=3.683; 95% CI: 2.106–6.441; p < 0.001), actively consulting the latest professional protection knowledge (aOR=2.962; 95% CI: 1.686–5.201; p = 0.001), and higher Knowledge scores (aOR=2.255; 95% CI: 1.294–3.930; p = 0.004) were independently associated with better practice scores. Conclusion Nurses in the orthopedic operating room had a positive attitude toward the occupational protection of using power tools, but their knowledge was insufficient, and their practice behavior was poor. Normative guidelines for occupational protection in the workplace of an orthopedic theatre and a training and evaluation system should be developed. Moreover, future measures should focus on education and training for occupational protection. Additionally, developing and designing occupational protective equipment that is more convenient for orthopedic surgery is important. Reporting method This research was designed as a cross-sectional survey study that was conducted in strict accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines.